Rendimiento de modelos de IA generativa en tres funciones docentes: análisis de tareas con CRP en ELE. - QI, WANYUN (Alfinge, 2025)
In response to the growing demand for Spanish professionals in China, this study explores the use of generative artificial intelligence in the teaching of Spanish as a foreign language (SFL). Using prepositional dependent constructions (PDC) as the object of analysis, the performance of six AI platforms was evaluated across three representative teaching tasks: exercise resolution, grammatical explanation, and activity design. Based on Español Moderno, a textbook widely used in Chinese universities, a set of standardized PDC exercises was selected and applied uniformly to all models, with task-specific instructions. The evaluation followed a set of predefined qualitative criteria. The results show that while all models completed the tasks, there were significant differences in accuracy, clarity, and pedagogical appropriateness. Each platform presents specific strengths and limitations depending on the task type, and some models showed difficulty in correctly interpreting task format or pedagogical intent. This study provides empirical insights into the potential and limitations of these tools and aims to offer guidance for their critical integration into SFL classrooms in China.